Left Ventricular Assist Devices Improve Functional Class without Normalizing Peak Oxygen Consumption. Issue 3 (May 2015) - Benton, Casey R.; Sayer, Gabriel; Nair, Ajith P.; Ashley, Kimberly; Domanski, Michael J.; Henzlova, Milena J.; Anyanwu, Anelechi C.; Pinney, Sean P.
Abstract : Heart failure patients supported with left ventricular assist devices (LVAD) enjoy improvements in functional capacity and quality of life. We reasoned that such improvements in exercise capacity should be reflected in an objective increase in peak oxygen consumption as measured by cardiopulmonary exercise testing (CPET). We performed a retrospective review of all recipients of a HeartMate II LVAD at our center from June 2009 to June 2012 who completed CPET. Thirty-seven patients completed CPET an average of 6 months after implantation. Of these, 10 patients had CPET performed before LVAD implantation. Overall, 91.4% of patients improved by at least two New York Heart Association classes, with 34.3% improving by three classes. Postimplant VO2 max was significantly less than predicted (14.7 ± 3.1 vs. 29.8 ± 6.6 ml/kg/min, p < 0.001; percent-predicted 51% ± 12%). For 10 patients with pre- and post-implant studies, VO2 max increased significantly from 11.6 ± 5.0 to 15.4 ± 3.9 ml/kg/min ( p = 0.009). VO2 max improves significantly with LVAD support but fails to normalize to predicted values, in spite of improvements in functional class. The severity of preimplantation heart failure does not associate with the degree of VO2 max improvement.